Can digital-free tourism build character strengths?. (November 2020) - Li, Jing; Pearce, Philip L.; Oktadiana, Hera
Abstract: The perception of digital-free tourism for developing character strengths was explored. A golden evidence triangle fusing the views of three respondent groups was established to assess trustworthy digital-free tourism-character strength linkages. Nine strengths were commonly acknowledged. They were distributed across a three-layer tiered model according to their relative importance. The strengths developed in digital-free tourism include: self-regulation, appreciation of beauty and excellence, social intelligence and open-mindedness for the core layer; vitality, love and perspective for the secondary layer; spirituality and creativity for the peripheral layer. The roles of each verified strength and the mechanisms for developing character strengths in digital-free tourism were captured in a three-stage travel narrative. Highlights: Digital-free tourism (DFT) defined and connected to positive psychology Tourists' perceptions of the links between DFT and character strengths explored Data-based tiered model summarises character strengths from digital-free tourism. Self-regulation, appreciation, social intelligence, and open-mindedness are core. Mechanisms operating are captured in the three-phases of travel.